Urgency of Recognizing Dayak Customary Communities and Land Rights in Central Kalimantan - Nathaniel, Ditto (Estudiante Law Journal, 2025)
This study found that there is a legal vacuum related to the determination of the Dayak Customary Law Community (MHA) as a legal subject along with legal vagueness related to the object of law, namely customary land based on regional regulation no.16/2008 Jo. PERDA No.1/2010 on Dayak customary institutions and PERGUB No.13/2009 Jo. PERGUB No.4/2012 on customary land and customary rights on land in Central Kalimantan, so that it does not meet the principle of legal certainty of customary land rights for Dayak Indigenous Peoples. This article aims to explain the urgency of establishing Dayak customary law and customary land rights for Dayak Indigenous people in Central Kalimantan. This study uses normative Research Methods with the approach of legislation, conceptual and historical.  Through the results of this study, it is advisable to immediately recognize and establish the Dayak Customary Law community as a subject of law through PERDA No. 2/2024 concerning recognition and protection of Dayak Customary Law communities and establishing Customary Land legal objects based on ATR/BPN regulation no. 14 of 2024 concerning the implementation of Land Administration and Land Registration of Customary Rights.